Quality of life and the associated factors among family caregivers of older people with dementia in Thailand. (1st July 2020) - Pothiban, Linchong; Srirat, Chomphoonut; Wongpakaran, Nahathai; Pankong, Orawan
Abstract: Long‐term care for older people with dementia can adversely impact a family caregiver's life. A decrease in their quality of life may compromise the quality of care they provide to older people and their own quality of life. The samples include 76 family caregivers of older people with dementia in Thailand. Six questionnaires and the EuroQoL Five Dimensions Questionnaire were used in data collection. Descriptive and inferential statistics were used in data analysis. The findings revealed that quality of life of family caregivers was at a high level. Experiences of close relationships between care dyads and perceived social support were positively related to family caregiver's quality of life, whereas perceived stress and burden were negatively related. Perceived social support and experiences of close relationships might be predictors of family caregiver's quality of life. High quality of life levels among Thai family caregivers of older people with dementia were influenced by high perceived social support and high experiences of close relationships. An intervention focusing on modifying such predicting factors may effectively help maintain quality of life of these family caregivers.